PENGEMBANGAN MODUL RELAKSASI UNTUK MENGURANGI KECEMASAN BELAJAR SISWA SMA - Merna Dianti; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to develop a relaxation module in order to reduce learning anxiety, especially high school students. The type of research used is research and development or Research and Development (R&D). Through 6 steps, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product creation. To make the module more perfect, this study conducted a validation test with 2 material experts and 2 practitioners. Data collection techniques in this study using literature study and validation questionnaires. The data analysis technique used qualitative and quantitative analysis. The results of the feasibility test of the module as a whole from the aspects of usability, feasibility and accuracy obtained an assessment of 73.95%, it shows that the relaxation module to reduce learning anxiety for high school students can be said to be feasible to be tested as an ingredient in providing BK services at school.Key Words: R&D, Relaxation Module ,Learning Anxiety